Functional phosphatome requirement for protein homeostasis, networked mitochondria, and sarcomere structure in C. elegans muscle - Lehmann, Susann; Bass, Joseph J.; Barratt, Thomas F.; Ali, Mohammed Z.; Szewczyk, Nathaniel J. (Wiley, 2017)
Background: Skeletal muscle is central to locomotion and metabolic homeostasis. The laboratory worm C. elegans has been developed into a genomic model for assessing the genes and signals that regulate muscle development and protein degradation. Past work has identified a receptor tyrosine kinase signalling network that combinatorially controls autophagy, nerve signal to muscle to oppose proteasome based degradation, and extracellular matrix based signals that control calpain and caspase activation. The last two discoveries were enabled by following up results from a functional genomic screen of known regulators of muscle. Recently, a screen of the kinome requirement for muscle homeostasis identified roughly 40% of kinases as required for C. elegans muscle health; 80 have identified human orthologues and 53 are known to be expressed in skeletal muscle. To complement this kinome screen, here we screen most of the phosphatases in C. elegans. Methods: RNAi was used to knockdown phosphatase encoding genes. Knockdown was first conducted during development with positive results also knocked down only in fully developed adult muscle. Protein homeostasis, mitochondrial structure, and sarcomere structure were assessed using transgenic reporter proteins. Genes identified as being required to prevent protein degradation were also knocked down in conditions that blocked proteasome or autophagic degradation. Genes identified as being required to prevent autophagic degradation were also assessed for autophagic vesicle accumulation using another transgenic reporter. Lastly, bioinformatics were used to look for overlap between kinases and phosphatases required for muscle homeostasis and the prediction that one phosphatase was required to prevent MAPK activation was assessed by Western blot. Results: A little over half of all phosphatases are each required to prevent abnormal development or maintenance of muscle. 86 of these phosphatase have known human orthologues, 57 of which are known to be expressed in human skeletal muscle. Of the phosphatases required to prevent abnormal muscle protein degradation, roughly half are required to prevent increased autophagy. Conclusions: A significant portion of both the kinome and phosphatome are required for establishing and maintaining C. elegans muscle health. Autophagy appears to be the mostly commonly triggered form of protein degradation in response to disruption of phosphorylation based signalling. The results from these screens provide measurable phenotypes for analysing the combined contribution of kinases and phosphatases in a multi-cellular organism and suggest new potential regulators of human skeletal muscle for further analysis.